Can ultrasound measurements of muscle thickness be used to measure the size of individual quadriceps muscles in people with patellofemoral pain?. Issue 1 (February 2015) - Giles, Lachlan S.; Webster, Kate E.; McClelland, Jodie A.; Cook, Jill
Abstract Objectives Selective atrophy of vastus medialis oblique (VMO) may be present in patellofemoral pain (PFP). This study investigated the validity of real-time ultrasound in measuring the thickness of each quadriceps muscle. Design Cross sectional-Validity. Setting University laboratory. Participants 10 limbs, 5 people with unilateral PFP. Main outcome measures The thickness of VMO, vastus lateralis (VL), vastus intermedius (VI), rectus femoris (RF), and vastus medialis (VM) measured with ultrasound were compared to magnetic resonance imaging (MRI) muscle thickness measurements, using Pearson's (r), and compared to MRI muscle cross-sectional area (CSA) measurements, using Spearman's correlation coefficient (rho). Results There was a good correlation between ultrasound and MRI measures of the thickness of each superficial quadriceps muscle VMO (r = 0.86), VM (r = 0.86), VL (r = 0.94), RF (r = 0.86), and a poor for VI (r = 0.37). Ultrasound measures had a good correlation to MRI muscle CSA measures for VL (rho = 0.83) and RF (rho = 0.88), moderate for VM (rho = 0.73), and poor for VMO (rho = 0.20), and VI (rho = 0.310). Conclusion Real-time ultrasound muscle thickness measurements are correlated to MRI measured thickness of superficial quadriceps muscles (VMO, VL, VL, and RF) in PFP.